Onomasiological and Semasiological Perspectives in Studies on Neology - Maroneze, Bruno; Lara Ganança, João Henrique (Linguistic Exploration, 2025)
This paper presents a theoretical and methodological model for applying the concepts of onomasiology and semasiology to studies on neology. The creation of a neologism can be seen as an onomasiological process (from concept to denomination), whereas the interpretation of a neologism may be regarded as a semasiological process (from denomination to concept). In other words, the creator of a neologism starts from the concept he/she has in mind to find the best way to express it linguistically (onomasiology); the decoder of a neologism, in turn, starts from a neological expression to identify the meaning(s) intended by it (semasiology). In analyzing a neologism from one perspective or the other, different questions may be asked: a) from an onomasiological point of view, what linguistic resources are available to the speaker to create a neologism with the intended meaning; what resources are best suited to the specific communicative intentions of the creator of a neologism; how do phonological, syntactic, semantic, and factors influence the choice of a lexical creation mechanism? b) from a semasiological point of view, what are the possible meanings of a given neologism; what mechanisms can the listener use to properly interpret a neologism? The argument is exemplified with the analysis of neologisms in the Base de neologismos do português brasileiro contemporâneo (Contemporary Brazilian Portuguese Neologism Database) and in the corpus of journalistic blogs that integrate Ganança’s dissertation.